Blockade of the costimulatory CD28‐B7 family signal axis enables repeated application of AAV8 gene vectors. (2nd March 2020) - Frentsch, Marco; Japp, Alberto Sada; Dingeldey, Manuela; Matzmohr, Nadine; Thiel, Andreas; Scheiflinger, Friedrich; Reipert, Birgit M.; de la Rosa, Maurus
Abstract: Adeno‐associated virus serotype 8 (AAV8) gene therapy has shown efficacy in several clinical trials and is considered a highly promising technology to treat monogenic diseases such as hemophilia A and B. However, a major drawback of AAV8 gene therapy is that it can be applied only once because anti‐AAV8 immunity develops after the first treatment. Readministration may be required in patients who are expected to need redosing, eg, due to organ growth, or to boost suboptimal expression levels, but no redosing protocol has been established. We have developed a preventive immune‐suppressive protocol for a human factor IX (FIX) vector with an intended dose of ~5 × 10 11  vg/kg that inhibits the development of anti‐AAV8 neutralizing‐antibody (NAb) responses and anti‐AAV8 T‐cell responses using CTLA4‐IgG (abatacept). In a preclinical model, transient treatment with abatacept during initial human FIX gene therapy efficiently inhibited the generation of AAV8‐specific cellular and humoral responses, and thus permitted redosing of FIX. Furthermore, our data suggest that by suppression of anti‐AAV8 NAb responses after the second higher dose (4 × 10 12  vg/kg) this protocol can be used to enable redosing up to such high doses. An additional advantage of CTLA4‐IgG blocking CD28‐mediated signals is its potential suppression of AAV8‐specific cytotoxic CD8 T‐cell responses, which are believed to kill transduced hepatocytes and might interfere with a successful readministration. Redosing protocols using approved drugs would be beneficial for patients because they could effortlessly be applied in clinical trials and enable safe and efficient treatment options for patients undergoing AAV8 gene therapy.